Métodos para la eliminación del exceso de flúor en agua de consumo casero - Guzmán Otalora, Valentina (Universidad Antonio Nariño, 2022)
The study of this document is carried out in Town Neiva, Huila, as is known according to the results obtained by the Departmental Health Secretary, the concentration of fluoride exceeds what is established in Decree 2115 of the Ministry of Health; Therefore, the objective of evaluating the effectiveness of peppermint and basil to reduce the concentration of fluoride in water is proposed. The development of the degree work was carried out under the HACH 8029 method, which consists of a reagent solution to determine fluorine in water, with the type of experimental study The results show that up to 72 hours of contact with the material the decrease in fluoride was achieved; but when it does not exceed this time, there is an increase in the release of fluoride.